Apple-derived miR-482a-3p decreases c-MYB expression and proliferation of human intestinal cell lines - Emanuela Pasculli; Marica Cariello; Maria Arconzo; Carla Gualtieri; Anca Macovei; Silvia Cultrera; Raffaella Maria Gadaleta; Elena Piccinin; Antonio Moschetta (PLoS ONE, 2026)
MicroRNAs (miRNAs) are small endogenous RNAs involved in gene expression modulation at post-transcriptional level, regulating several biological processes ranging from differentiation to proliferation and preservation of cell and tissue identity. Evidence describe the ability of miRNAs to move between organisms of distinct species, a phenomenon referred to as “trans-kingdom” exchange. Notably, plant miRNAs can be transferred to other species, including humans, and potentially target and modulate genes. Here, we investigated for the first time the trans-kingdom capability of apple-derived microRNAs (miRNAs) to influence human intestinal cells (HT-29 and HCT116) in vitro . Our data demonstrate that synthetic apple-derived miR-482a-3p and miR-858 can be internalized by human colonic cell lines and significantly reduce cell proliferation. Through an in silico analysis followed by gene expression and luciferase reporter assays, we show that apple-derived miR-482a-3p targets the human c-MYB gene in intestinal cell lines, thereby directly contributing to the regulation of the enterocyte cell cycle. This study supports the trans-kingdom hypothesis by providing evidence that plant-derived miRNAs can directly modulate enterocyte lifespan and metabolic activity.